Improving The Modulus of Elasticity of High Performance Concrete by Using Steel Fibers - A.Salih, Shakir (Anbar Journal of Engineering Sciences, 2012)
The aim of this paper is to study experimentally the effect of steel fibers content on the modulus of elasticity of High Performance concrete HPC in different curing age. The results showed that adding steel fibers to HPC led to a considerable improvement in static and dynamic modulus of elasticity where at 90 day water curing the percentages of increasing in static modulus of elasticity of High Performance Steel Fiber Concrete HPSFC relative to HPC were 8.2%, 9.98%, and 11.88% at 0.5%, 1%, and 1.5% steel fibers by total concrete volume, respectively. While, the improvement of dynamic modulus of elasticity of HPSFC relative to HPC at 28 day were 8.09%, 10.7%, and 11.07% % at 0.5 %, 1 %, and 1.5 % respectively.